An Impact Assessment of The Effectiveness of Utilizing Informal Health Communication Interventions to Spread Health Recommendations and Change Public Perception - Abdel Mawgoud, Lina Mohamed Ezzat Ahmed (AUC Knowledge Fountain, 2026)
Brain health is an increasingly urgent but critically under-addressed public health priority in Egypt and the wider MENA region. Despite its centrality to aging, productivity, and overall quality of life, public understanding of brain health remains limited, and stigma continues to shape responses to dementia and cognitive decline. This study evaluates the effectiveness of informal, culturally adapted health communication as a tool to shift perception, increase awareness, and promote behavior change among non-medically trained adults in Egypt. Grounded in global evidence on cognitive reserve, neuroplasticity, and the life-course approach to brain health, the intervention translated expert-informed brain health recommendations into an Arabic-language, community-based workshop. The pilot was implemented in Cairo and Alexandria, engaging 20 participants through an accessible, dialogue-based format. Pre- and post-intervention data were collected using a validated Arabic assessment tool featuring Likert-scale and open-ended items. Quantitative analysis employed Wilcoxon Signed-Rank tests and frequency analysis to assess changes in knowledge, motivation, and behavioral intent. Results showed statistically significant improvements across all key domains. Participants demonstrated increased frequency of thinking about brain health (p = 0.001), greater likelihood of adopting protective lifestyle behaviors such as exercise, sleep hygiene, and nutrition (p < 0.05), and enhanced willingness to seek help or share information with others. Qualitative data corroborated these findings, revealing shifts in attitudes toward dementia, heightened empathy for caregivers, and enthusiasm for continued learning. Notably, participants expressed a sense of empowerment and ownership over their cognitive well-being, reflecting the impact of the informal and culturally relevant delivery model. This intervention underscores the potential of peer-led, community-based brain health education in medically underserved settings. It marks the foundational phase of El Feed El Mofeed, a broader Arabic-language science communication platform. The first program under this umbrella, Mind Lab, offers a scalable model that bridges the gap between evidence-based knowledge and everyday health practice. By centering cultural resonance, emotional safety, and accessibility, this research contributes to a growing field of informal health communication and advocates for inclusive, locally adapted strategies to promote brain health equity across the MENA region.